Application of Picture and Picture Type for Increasing Students' Creativity in Science Subjects - Eldawati, Eldawati (Program Magister Teknologi Pendidikan Universitas Jambi, 2020)
This research aims to find out whether using the picture and picture learning type in science subjects in class IV elementary school 13/1 Muara Bulian can increase students' creativity in learning. This type of research is Classroom Action Research which is carried out in cycle III. Each cycle has 2 meetings attended by 25 students which is carried out in class IV of elementary school 13/1 Muara Bulian. Data collection techniques in this research are observation and questionnaires. From the research results obtained, the average value of student creativity in cycles I (60), cycles II (79) and III (84), we can see that students' creativity continues to increase each cycle by using the picture and picture learning type. So it can be concluded that using the picture and picture type cooperative learning model can increase students' creativity in learning. The author suggests using a learning model in the learning process that is appropriate to the material being taught.